Obsessive-compulsive symptoms in medical students: prevalence, severity, and correlates - Torres, Albina R. [UNESP]; Cruz, Bruna L. [UNESP]; Vicentini, Henrique C. [UNESP]; Lima, Maria Cristina P. [UNESP]; Ramos-Cerqueira, Ana Teresa A. [UNESP] (Springer, 2015)
The study aims were to estimate the prevalence and correlates of symptoms suggestive of obsessive-compulsive disorder (OCD) among medical students and investigate the severity and correlates of specific obsessive-compulsive symptom (OCS) dimensions in this population. A cross-sectional study with 471 Brazilian medical students, who were assessed using the Obsessive-Compulsive Inventory-Revised (OCI-R). The main outcomes were probable OCD (OCI-R score >27) and overall/dimensional OCI-R scores. Sociodemographic data, depressive symptoms, and several aspects of academic life were also investigated. Bivariate analyses were followed by regression models. Eighteen (3.8 %) participants presented probable OCD, which was associated with depression. The mean OCI-R score was 8.9, and greater overall severity was independently associated with being a freshman, difficulty in adaptation, and depressive symptoms. Higher scores in the checking and washing dimensions were associated with being a freshman, in the neutralization and ordering dimensions with adaptation difficulties, and in the hoarding dimension with adaptation difficulties and depressive symptoms. The obsession dimension was associated with being a freshman, difficulty making friends, depressive symptoms, and psychological/psychiatric treatment. Probable OCD is more frequent in medical students than in the general population and is associated with depressive symptoms. Efforts are required to identify OCS in this population, particularly among first-year students and to provide treatment, when necessary. Institutional programs that properly receive freshmen, enhancing their integration with other colleagues and their adaptation to the city, may decrease the level of stress and, consequently, OCS severity.
Keywords: Medical students; Emotional problems; Medical students; Behavioral sciences; Obsessive-compulsive symptoms; Obsessive-compulsive disorder; Mental health